Pengaruh Konsentrasi dan Lama Perendaman H2SO4 terhadap Pematahan Dormansi Benih Kopi Arabika (Coffea arabica L.) Varietas Kopyol - BINARHT, NOVIAN NAFI; MAYUN, IDA AYU; ASTAWA, I NYOMAN GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.2, April 2022, 2022)
Effect  of   H 2 SO 4  Concentration  a nd Soaking Time On Dormancy Breaking  o f Arabica Coffee ( Coffea arabi c a  L.) Kopyol Varieties This study aims to determine the effect of H 2 SO 4  concentration and soaking time on breaking the dormancy of Kopyol Arabica coffee. The experimental design used was a factorial randomized block design with two factors. The first factor is the concentration of H 2 SO 4 , which consists of four levels, namely 0%, 10%, 20% and 30%, while the second factor is the immersion time, which consists of three levels, namely 10 minutes, 20 minutes and 30 minutes. The research was conducted at Mengani Village, Kintamani District, Bangli Regency, from August 2021 to October 2021. The results showed the interaction of H2SO4 concentration treatment and immersion time had a significant effect on the germination variable (%), maximum growth potential (%), dormancy intensity (%) and synchronous growth (%) and had no significant effect on the growth speed (%/etmal) variable. The best treatment for accelerating the breaking of dormancy is the treatment with 20% H2SO4 concentration and 20 minutes of soaking time, which breaks dormancy at 25 days after sowing and has a germination value of 91.11%, a maximum growth potential of 97.78%, a dormancy intensity of 2.22% and synchronous growth of 86.67% compared to the control, which broke dormancy at 35 days after sowing and had a germination value of 57.78%, a maximum growth potential of 64.44%, a dormancy intensity of 35.56% and synchronous growth of 53.33%.